2020
DOI: 10.1159/000511383
|View full text |Cite
|
Sign up to set email alerts
|

OVOL1/2: Drivers of Epithelial Differentiation in Development, Disease, and Reprogramming

Abstract: OVOL proteins (OVOL1 and OVOL2), vertebrate homologs of <i>Drosophila</i> OVO, are critical regulators of epithelial lineage determination and differentiation during embryonic development in tissues such as kidney, skin, mammary epithelia, and testis. OVOL can inhibit epithelial-mesenchymal transition and/or can promote mesenchymal-epithelial transition. Moreover, they can regulate the stemness of cancer cells, thus playing an important role during cancer cell metastasis. Due to their central role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…We observed that these PSFs maintained the enrichment of hybrid E/M phenotypes in stem-like traits, endorsing the robustness of this association. Consistently, many of these PSFs have been reported to play a functional role in maintaining more epithelial phenotypes (e, he) as well as stemness in experiments in cancer cell lines and in cellular reprogramming contexts involving the modulation of EMP [ 53 , 77 , 78 ]. GRHL2 and OVOL2 have also been proposed as MET-inducing transcription factors (MET-TFs), but our simulations suggest that their ability to induce a “complete” MET need not be universal.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We observed that these PSFs maintained the enrichment of hybrid E/M phenotypes in stem-like traits, endorsing the robustness of this association. Consistently, many of these PSFs have been reported to play a functional role in maintaining more epithelial phenotypes (e, he) as well as stemness in experiments in cancer cell lines and in cellular reprogramming contexts involving the modulation of EMP [ 53 , 77 , 78 ]. GRHL2 and OVOL2 have also been proposed as MET-inducing transcription factors (MET-TFs), but our simulations suggest that their ability to induce a “complete” MET need not be universal.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to being thought of as PSFs, GRHL2 and OVOL1/2 have been considered as Mesenchymal-Epithelial Transition (MET)-inducing transcription factors (MET-TFs), as their overexpression in carcinomas is capable of upregulating the expression levels of E-cadherin and/or revert EMT [ 50 , 51 , 52 , 53 , 54 ] as well as other EMT-associated traits, such as anoikis resistance, metabolic reprogramming [ 55 ], and immune evasion [ 56 ]. This observation is consistent with their knockdown known to drive a “full” EMT in both cancer cell lines and in developmental contexts [ 46 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the context of cancer, cells with punctate E-CADHERIN localization represent an intermediate epithelial-mesenchymal state ( Sha et al, 2019 ; Yang et al, 2020 ), characterized by an increased propensity for collective invasion and metastasis ( Aiello et al, 2018 ; Ayollo et al, 2009 ; Gloushankova et al, 2017 ; Jolly et al, 2015 ; Kovac et al, 2018 ; Saitoh, 2018 ). This state is linked to the downregulation of the transcription factor Ovol1 ( Jia et al, 2015 ; Saxena et al, 2020 ), which suppresses a mesenchymal identity, and the tight junction component, Claudin7 ( Aiello et al, 2018 ; Kim et al, 2019 ; Wang et al, 2018 ). Both of these factors were also significantly downregulated in Rreb1 -/- embryos ( Figure 6—figure supplement 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…To address this question we assessed the levels of a panel of five well-studied EMT-inducing or EMT-associated factors – SNAI1, SNAI2, ZEB1, ZEB2, and TWIST1 (Subbalakshmi et al 2021; J. Yang et al 2004; Drápela et al 2020; Vandewalle 2005) – and five MET-inducing or MET-associated factors – GRHL2, OVOL1, OVOL2, ESRP1, and ESRP2 (Saxena et al 2020; Cieply et al 2012; Jolly et al 2018; Jeong et al 2017; Fici et al 2017) – across tumor types.…”
Section: Resultsmentioning
confidence: 99%